PSYCHOLOGICAL FEATURES OF PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY (Web of Teachers: Inderscience Research, 2025)
The article discusses the psychological factors of student professional formation in the team of educational institutions. The article analyzes the topical issue of the relationship between the level of motivation to achieve success, self-esteem and personal characteristics of students.